Investigations on efficiency improvement of rolling piston type rotary compressor with a new-designed cylinder. (5th March 2023) - Meng, Xiangqi; Qi, Yingxia; Sheng, Lei; Li, Qingpu; Su, Lin
Highlights: Proposed a new cylinder design for rolling piston type rotary compressor. Temperature and heat flux measurements conducted on cylinder outer walls. Cylinder inner wall temperature reduced by as much as 7 °C. Volumetric and electrical efficiencies increased by 3.5% and 4.4% respectively. Abstract: Excellent cylinder thermal characteristics is important to improve the efficiency of rolling piston type rotary compressors, thus a new-designed cylinder was proposed to increase the heat transfer of the cylinder to the external ambient. The temperatures on the inner-wall of the original cylinder, the temperatures and heat fluxes on the outer-wall of the new-designed cylinder were measured. Then the influences of the cylinder thermal characteristics on the volumetric and electrical efficiencies of the original and new-designed compressors were analyzed. The experimental results show that the inner-wall temperatures of the new-designed cylinder were decreased by 7.0 °C at maximum compared to the original one, and the temperature drop was increased along with the rotation angle of the rolling piston in an approximately linear way. Consequently, the volumetric and electrical efficiencies of the new-designed compressor were increased by 3.52 % and 4.43 %, respectively. This study would be helpful to improve the efficiencies of rolling piston type rotary compressors.